Sensitivity of PCR IS6110 in relation to culture and staining in Pott’s disease - Arun Kumar Srivastava; Vijaya Lakshmi Nag; Anand Kumar Maurya; Tapan N. Dhole; Sunil G. Babu (Indian Journal of Neurosurgery)
Background Rapid diagnosis is essential to decrease the morbidity and mortality of Pott’s disease. The bacteriological methods are time-consuming or insensitive. Polymerase chain reaction (PCR) provides a rapid diagnostic tool and hope for early diagnosis of this disease. The aim of this study was to compare and assess of a rapid and effective method among diagnostic battery (Ziehl–Neelsen (ZN) microscopy, BACTEC culture and PCR) of Pott’s disease.